2021
DOI: 10.21037/tcr-21-37
|View full text |Cite
|
Sign up to set email alerts
|

Construction of five microRNAs prognostic markers and a prognostic model for clear cell renal cell carcinoma

Abstract: Background: To determine the role of miRNA in the progression and outcome of renal clear cell carcinoma (ccRCC), establish a model for predicting outcome in patients with ccRCC and verify it using a Cox regression model. The miRNA target genes were predicted to understand their biological functions.Methods: The microRNAs of 71 normal tissues and 545 tumor tissues were downloaded from TCGA (https://tcga-data.nci.nih.gov/tcga/). We also downloaded 537 clinical materials from this website. The miRNA difference an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Levels of this miRNA were found to be higher in sunitinib resistant cells when compared with parental ones [45]. In agreement with our results, the work of Zhou et al, using the TCGA database, showed that high expression levels of miR-130b in renal tumour samples were related to worse survival [46]. We also demonstrated that down-regulation of FLT1, PRDM1 and SAV1 were significantly associated with non-responsive ccRCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Levels of this miRNA were found to be higher in sunitinib resistant cells when compared with parental ones [45]. In agreement with our results, the work of Zhou et al, using the TCGA database, showed that high expression levels of miR-130b in renal tumour samples were related to worse survival [46]. We also demonstrated that down-regulation of FLT1, PRDM1 and SAV1 were significantly associated with non-responsive ccRCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…MiR-155-5p has also been demonstrated to mediate characteristics of ccRCC progression such as proliferation, migration, and invasion [13,44,45]. Furthermore, other studies have examined the utility of miR-155-5p as a biomarker for prognostic outcomes in those with ccRCC [48,49]. Beyond prognosis, a recent paper by Sequeira et al 2022 found that miR-155-5p aided in accurate detection of RCC from patient plasma [50].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were seeded into 35 mm dishes (Corning Costar Corporation, Cambridge, MA, USA) in duplicate at a density of 2 × 10 4 cells/mL, determined using a hemocytometer (American Optical Corporation, Buffalo, NY, USA). Forty-eight [48] hours after culturing, RealTime-Glo™ MT Cell Viability Assay (Promega, Madison, WI, USA) reagents were added to each dish at a 1:2000 dilution. Luminescence readings were obtained utilizing the GloMax ® 20/20 Luminometer (Promega, Madison, WI, USA) 1 h after the addition of the Cell Viability reagents.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…The function of miR-1251-5p is the only establishment. In ovarian cancer cells, by addressing the tumor suppressor TBCC, Zhou et al [ 8 ] found that miR-1251-5p increased carcinogenesis and autophagy. However, it is unknown if miR-1251-5p performs a function in developing HCC [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-1251-5p was found on chromosome 12q23.1, but there were few studies about this miRNA in ccRCC. Liang et al [ 7 ] and Zhou et al [ 8 ] have confirmed that miR-1251-5p is a prognostic factor of ccRCC based on database analysis, but no experimental verification has been carried out and only TCGA database has been used for analysis. The activity of miR-1251-5p is upregulated with hepatocellular carcinoma cells, according to a microarray study of miRNAs, and could represent a viable therapeutic target for therapy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%